Sharing a Ride on the Commodities Roller Coaster: Common Factors in Business Cycles of Emerging Economies - Andrés Fernández; Andrés González; Diego Rodríguez (Inter-American Development Bank (IDB), 2015)
Fluctuations in commodity prices are an important driver of business cycles in small emerging market economies (EMEs). This paper documents how these fluctuations correlate strongly with the business cycle in EMEs. A commodity sector is then embedded into a multi-country EMEs business cycle model where exogenous fluctuations in commodity prices follow a common dynamic factor structure and coexist with other driving forces. The estimated model assigns to commodity shocks 42 percent of the variance in income, of which a considerable part is linked to the common factor. A further amplification mechanism is a spillover effect from commodity prices to risk premia.
hdl:11319/7382
Keywords: E32; F41; F44; 330; Emerging economies; Business cycles; Commodity prices; Common factors; Bayesian estimation; Dynamic stochastic equilibrium models